Controlled drug release characteristics and antibacterial influence of streptomycin sulfate-loaded PMMA/PEO/bis-chalcone derivatives-based fibers - Maslakci, Neslihan Nohut; Eren, Esin; Kocer, Kadinsah Nur; Cevikbas, Halime; Ulusoy, Seyhan; Bicer, Abdullah; Cin, Gunseli Turgut (Elsevier, 2022)
The aim of this study is to fabricate streptomycin sulfate (STM)-loaded bis-chalcone/poly(methyl methacrylate) (PMMA)/poly(ethylene oxide) (PEO) based fiber mats for drug delivery and antibacterial applications. This study presents the synergetic effect of a bis-chalcone derivatives ((2E,6E)-2,6-bis[(thiophen-2-yl)methylene]cyclohexanone (BTC) or (2E,6E)-2,6-bis(4-nitrobenzylidene)cyclohexanone (BNC)) to STM loading and antibacterial properties of fibers. Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy and energydispersive X-ray spectroscopy (SEM/EDS) were employed to characterize diverse features of the prepared electrospun fibers, namely, morphology, elemental composition, structures of the molecular chains. The longest drug release profile was observed for PMMA/PEO/BTC-STM60 fiber (77.6% for 33,120 min) compared to the other fiber samples. According to the drug release results, PMMA/PEO/BTC-STM60 is the most preferable electrospun fiber to provide a prolonged release for 33,120 min rather than the immediate release of STM. The antibacterial effects of drug-containing and non-drug fibers against Bacillus cereus and Escherichia coli were investigated. It was observed that the drug-free fibers did not have any antibacterial effect, while the drug-containing fibers completely inhibited the growth of B. cereus and E. coli. Our findings can provide insight into new fibers prepared with antimicrobial compounds for drug release based wound dressing applications.
Keywords: Streptomycin sulfate; Drug release; Antibacterial; Electrospun fiber